Attractiveness, Anthropometry or Both? Their Relationship and Role in Economic Research - Sonia Oreffice; Climent Quintana-Domeque (Fondazione Eni Enrico Mattei (FEEM), 2014)
We analyze how attractiveness rated at the start of the interview is related to weight (controlling for height), and BMI, separately by gender and also accounting for interviewer fixed effects, in a nationally representative sample. We are the first to show that height, weight, and BMI all strongly contribute to male and female attractiveness when attractiveness is rated by opposite-sex interviewers, whereas only thinner female respondents are considered attractive by same-sex interviewers; that is, anthropometric characteristics are irrelevant to male interviewers in assessing male attractiveness. In addition, we estimate the interplay of these attractiveness and anthropometric measures in labor and marital outcomes such as hourly wage and spousal education, showing that attractiveness and height matter in the labor market, whereas both male and female BMI are valued in the marriage market instead of attractiveness.
Keywords: D1; J1; 330; Beauty; BMI; Height; Weight; Wage; Spousal Education